2009
DOI: 10.1007/s10803-009-0733-4
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Behavioral Characteristics of Children with Rubinstein-Taybi Syndrome

Abstract: Research regarding the behavioral aspects of children with Rubinstein-Taybi syndrome (RTS) has suggested some possible behavioral patterns including autistic features. Caregivers of 39 children (mean age = 8.4 years) with RTS (49% showing abnormality in CREBBP gene) and 39 children (mean age = 8.6 years) matched on developmental level, age and gender were administered the Child Behavior Checklist and the Children's Social Behavior Questionnaire. Children with RTS did not exhibit higher internalizing (affective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 21 publications
3
59
0
2
Order By: Relevance
“…Over 75 % were reported to insist on sameness. Recently, Galéra et al (2009) reported higher rates of repetitive motor movements in contrast to a heterogeneous intellectual disability group; however, because this study did not contain syndrome specific comparison groups, conclusions cannot be drawn about how these repetitive behaviors compare to behaviors observed in other syndromes. A systematic cross syndrome approach to studying repetitive behavior in RTS is absent from the literature.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Over 75 % were reported to insist on sameness. Recently, Galéra et al (2009) reported higher rates of repetitive motor movements in contrast to a heterogeneous intellectual disability group; however, because this study did not contain syndrome specific comparison groups, conclusions cannot be drawn about how these repetitive behaviors compare to behaviors observed in other syndromes. A systematic cross syndrome approach to studying repetitive behavior in RTS is absent from the literature.…”
Section: Introductionmentioning
confidence: 86%
“…Individuals with RTS could present with a dissociation of ASD characteristics: repetitive behavior without, or with fewer, social-communication impairments. This is because people with RTS may have fewer social deficits than individuals with ASD as parents often describe RTS children as friendly, particularly around adults (Goots and Liemohn 1977;Baxter and Beer 1992;Stevens et al 1990), and reports suggest a greater degree of sociability in RTS relative to controls (Galéra et al 2009;Nelson 2010). While, social behavior is not the main focus of this study, correlational analyses exploring the link between repetitive behavior, social-communication deficits, and degree of disability will be conducted to explore the factors associated with the repetitive behavior profile of RTS.…”
Section: Introductionmentioning
confidence: 99%
“…Sixty percent of neurologically typical children show some stereotypic movements or behaviors between 2 and 5 years (8, 9). Besides the physiological ones, stereotypies are a main symptom of several developmental disorders, such as autistic spectrum disorder (ASD), intellectual disabilities (ID), genetic syndromes (Rett syndrome, Lesch–Nyhan syndrome, X-fragile syndrome, and others), and are also reported in sensory impaired individuals (1012). In particular, stereotypies, together with other restricted, repetitive patterns of behavior, interest, or activities, represent a core symptom of ASD (13).…”
Section: Introductionmentioning
confidence: 99%
“…The abnormality in CREB BP gene is probably related to the impaired motor skills learning. 3,8 On application of the CARS, we found autistic behavior in the index case. Sensory processing dysfunction, especially tactile sensitivity, is commonly found in autism.…”
Section: Discussionmentioning
confidence: 88%